2012
DOI: 10.1002/pc.22248
|View full text |Cite
|
Sign up to set email alerts
|

PES/SiO2 nanocomposite by in situ polymerization: Synthesis, structure, properties, and new applications

Abstract: SiO2 nanoparticles of a quantum size (15 nm or less) were prepared via sol–gel method using tetraethylorthosilicate as a precursor. SiO2 nanoparticles were characterized by X‐ray diffraction (XRD) and field‐emission scanning electron microscopy (FESEM) analyses. Polyethersulfone/silica (PES/SiO2) crystal structure nanocomposite was prepared by in situ polymerization using silica nanoparticles as reinforcement filler. The polymerization reaction was done at 160°C in paraffin bath in the presence of diphenolic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…30 The T g in membrane is affected by region of free volume and chain mobility existed between the nanoparticles and polymer molecules due to the attractive or repulsive interaction. This result is in agreement with Shariatmadar et al 32 in which they also found that the addition of SiO 2 nanoparticles in the PES matrix could increase the thermal resistance of the membranes. 31 Table 2 shows the DSC results for the membranes incorporated with different concentration of modied SiO 2 .…”
Section: Thermal Stability Of the Membranessupporting
confidence: 92%
“…30 The T g in membrane is affected by region of free volume and chain mobility existed between the nanoparticles and polymer molecules due to the attractive or repulsive interaction. This result is in agreement with Shariatmadar et al 32 in which they also found that the addition of SiO 2 nanoparticles in the PES matrix could increase the thermal resistance of the membranes. 31 Table 2 shows the DSC results for the membranes incorporated with different concentration of modied SiO 2 .…”
Section: Thermal Stability Of the Membranessupporting
confidence: 92%
“…Nano-reinforced polymers have had increasing interest from the research community over the past decade [1][2][3]. A nanocomposite is a category of composites with a reinforcing phase consisting of inclusions with at least one nano-sized dimension [4][5][6][7]. The use of a small amount of nanostructured reinforcements in polymers has the potential to improve the mechanical and physical properties relative to traditional reinforcements [8][9][10][11][12], among which glass and carbon fibers are the most common materials [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various mesoporous and nano-adsorbents are used for water treatment. [1][2][3][4][5] There have been increasing demands for the application of novel carbonaceous materials in water treatment due to their low cost and high efficiency. Several methods have been used for the preparation of synthetic carbons, such as carbonization, electro-spinning, laser ablation and hydrothermal carbonization.…”
Section: Introductionmentioning
confidence: 99%